Parents perceptions of stress in a neonatal intensive care unit in Rwanda - Priscille Musabirema; Petra Brysiewicz; Jennifer Chipps (AOSIS, 2015)
Background: Having a newborn infant hospitalised in the neonatal intensive care unit (NICU) is an unexpected and stressful event for a family. A number of potential stressors to which family members of patients in these units may be exposed have been identified, although no studies about this issue have been conducted in Rwanda. Aim: The aim of this study was to describe and analyse parental perception of stress that resulted from having their infant admitted to a NICU in Kigali, Rwanda. Method: A quantitative survey was used to describe and analyse parents' perceptions of stress when they had an infant admitted to a NICU. The Parental Stress Scale: Neonatal Intensive Care Unit was used to measure the level of stress that those parents experienced. Results: The results indicated that parents experienced stress from having their infants cared for in a NICU. The most stressful events were the appearance and behaviour of the baby with a mean score of 4.02, whilst the subscale items related to sights and sounds were found to be the least significant source of stress for parents with a mean score of 2.51. In addition, the current study found that parents' age, educational level, occupation, and infant birth weight were associated with parental stress. Conclusion: The study established that a range of factors was responsible for parental stress when a baby was cared for in a NICU. Identification of these factors could enable health professionals from a hospital in Kigali, Rwanda, to facilitate parents' adjusting and coping.